Pemanfaatan Teh Daun Sacha Inchi Berbasis Analisis Organoleptik untuk Mendukung Kemandirian Ekonomi Masyarakat Desa Cikancung: Penelitian - Ananda Rachmaniar; Nugraha Nurul Patah; Yeyen Nenden Hermawati; Fawzi Fatah Ramdhan; Muthahharah Thahir (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Sacha Inchi plant possesses significant potential as it contains antioxidants, omega-3, omega-6, omega-9, saturated fats, and other bioactive compounds that are beneficial to human health. However, its utilization within the community remains limited, resulting in suboptimal economic value. This issue is addressed through an innovation that processes Sacha Inchi leaves into competitive herbal tea. The development process was conducted using a scientific approach, employing the Multi Factor Evaluation Process (MFEP) method along with organoleptic testing, which assessed aspects such as color, aroma, taste, aftertaste, infusion clarity, and the physical characteristics of the leaves. The results of the panelist evaluation and MFEP analysis indicated that the drying treatment using envelopes, whether outdoors (OUT A) or indoors (IN A), yielded the best organoleptic quality, particularly in terms of taste, aroma, and infusion clarity. This method was proven effective in preserving leaf pigments and bioactive compounds while simultaneously enhancing consumer acceptance. In addition to producing high-quality tea, this study successfully developed a tangible product in the form of star peanut leaf tea with attractive, hygienic packaging that is ready for market distribution. These findings demonstrate that innovations based on local resources not only contribute to the advancement of functional food products but also provide added economic value and support the empowerment of the Cikancung Village community.